Effective English Teaching Strategies for Deaf Students: A Study at SMP SLB Negeri 1 Buleleng - Aprilia Hana Nenepat; I G A Lokita Purnamika Utami; Ni Luh Era Adnyayanti (Journal of Educational Study, 2026)
This study explores the strategies used by teachers, how these strategies are applied in the classroom, and the challenges that appear during the learning process. Using a qualitative descriptive approach, data were collected through interviews and classroom observations. The findings show that visual based methods such as the use of Sign Language SIBI, kinesthetic strategies, and various forms of visual media play an important role in improving students’ understanding of English. Sign Language provides clear visual cues that help increase students’ confidence and motivation, while visual and kinesthetic activities make lessons more engaging and easier to follow. However, the application of these methods is still limited by the lack of teaching materials, differences in language structure, and teachers’ varying mastery of instructional techniques. This study highlights the importance of teacher preparation, the development of inclusive learning resources, and the use of technology to support the English learning needs of deaf students. Overall, the findings underline the need to create an inclusive learning environment that offers equal opportunities for students with special needs.